Experimental investigation of scatter in fracture toughness data of SA516Gr.70 steel in the ductile-to-brittle transition regime for high rate of loading using split Hopkinson pressure bar test setup. (April 2021) - Sharma, S.; Samal, M.K.
Highlights: Split Hopkinson pressure bar is used to conduct tests on sub-sized SE(B) specimens. Tests are conducted with impact velocity of 700 m/min in the range of −100 to −60 °C. Median value, scatter in fracture toughness increase with temperature in DBTT regime. Scatter is fracture toughness data is bounded well by 5% and 95% master curves. Transition temperature T0 of these tests is high when compared to quasi-static tests. Abstract: Ferritic grade steels exhibit ductile to brittle transition in the sub-zero temperature regime and the fracture toughness data show scatter and temperature dependence. The fracture toughness variation also depends upon rate of loading in addition to neutron irradiation, specimen geometry and loading configuration. The material SA516Gr.70 steel is widely used in nuclear industry as material of transportation cask, vessels and piping etc. The study of the effect of rate of loading on the fracture toughness transition curve in the ductile-to-brittle transition regime of this material is important for designers and safety analysts. In this work, the split Hopkinson pressure bar test technique has been used to carry out fracture tests on sub-sized single-edged notched bend specimens in the temperature range of −100 to −60 deg. C by loading the specimens at a very high loading rate of 700 m/min. This loading rate is at least 6 orders of magnitude higher than the rates (i.e., fraction of mm/min) employed for quasi-static fracture tests. The strain pulses, during high rate of loading, have been captured through strain gages located in the incident and transmission bars of the test setup. The load–displacement data for the specimens have been evaluated from the strain signal and these have been used to evaluate fracture toughness for onset of cleavage fracture in terms of KJc . The scatter and temperature dependence of the data have also been modelled through Weibull's statistical distribution and master curve bounds according to ASTM E1921. From the results of fracture experiments, it was observed that the fracture transition temperature T0 increased significantly for the high rate of loading when compared to quasi-static data of similar materials in literature. This observation has been explained in terms of micro-mechanism of the cleavage fracture in the process zone ahead of crack-tip which changes due to rate of loading. This study indicates that the rate of loading is an important parameter in the design and integrity analysis of ferritic grade steel components in addition to other parameters such as specimen geometry and loading conditions.